Rapid measurement of total lipids in zooplankton using the sulfo-phospho-vanillin reaction. Issue 27 (24th June 2022) - Pinger, Cody; Copeman, Louise; Stowell, Michelle; Cormack, Bryan; Fugate, Corey; Rogers, Matthew
Abstract : Here, we analyze the performance of a microplate assay utilizing the sulfo-phospho-vanillin (SPV) reaction to quantify the total lipid content of various large crustacean zooplankton in a rapid and high throughput manner. Abstract : Zooplankton provide a vital source of nutrition to a variety of fish and marine predators. Measuring the total lipid content of zooplankton provides important information about diet quality available to predators, revealing details about trophic dynamics and ecosystem status. We analyze the performance of a microplate assay, utilizing the sulfo-phospho-vanillin (SPV) reaction, to quantify the total lipid content of various large crustacean zooplankton in a rapid and high throughput manner. Pilot experiments were performed by measuring the total lipid content of purchased freeze-dried zooplankton ( Calanus finmarchicus and Euphausia superba ) by both SPV and gravimetric analysis (low throughput and requires large sample size). The results of the SPV assay were not statistically different from gravimetric analysis for either species ( p > 0.05). Further, an inter-laboratory comparison study was performed to measure the total lipid content (% of wet mass) of field-collected Arctic and North Pacific zooplankton (copepods ( n = 19) and euphausiids ( n = 29)) of various species utilizing multiple analysis methods. Results from thin layer chromatography with flame ionization detection (TLC-FID) demonstrated that lipid classes in zooplankton samples varied in composition of steryl/wax esters (3–95%), triacylglycerols (1–52%), free-fatty acids (0.4–25%), sterols (0–4%) and polar lipids (1–42%). Despite this variation in lipid class composition among samples, the results of the SPV assay agreed well with gravimetric analysis. The mean absolute and relative differences between SPV and gravimetric analysis for all zooplankton lipids in this study were 1.0% and 11.6%, respectively. The SPV assay is rapid (<2 hours), high throughput (25 samples processed in parallel), low cost (supplies <$ 0.67 per sample), precise (inter assay CV = 6.9%, intra assay CV = 6.0%), sensitive (limit of detection < 1.7 micrograms of lipid per analysis), and accurate when calibrated with appropriate standards.